Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/ans.17028
|View full text |Cite
|
Sign up to set email alerts
|

The need for improved patient reported outcome measures in patients with extremity sarcoma: a narrative review

Abstract: Background: Extremity sarcoma causes impairments to functionality and quality of life. Patient-reported outcome measures (PROMS) assess patient perspectives relating to domains of health and quality of life. Methods: To describe PROMs utilised in extremity sarcoma, the available literature was screened for studies that utilised PROMs to evaluate outcomes in extremity sarcoma following surgery. Results: Seventy articles met eligibility criteria; six PROMs were identified. The Toronto Extremity Salvage Score, Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Despite its advantages and superiority over other PROMs in assessing functional outcome, the TESS remains solely a subjective measure and given that it was developed almost 20 years ago, its applicability for the modern environment has been questioned. Blight and Choong in particular suggested that it should be further refined to accommodate more recent surgical innovations, 39 a common theme across most subjective methods of functional outcome assessment.…”
Section: Subjective Functional Outcome Assessmentmentioning
confidence: 99%
“…Despite its advantages and superiority over other PROMs in assessing functional outcome, the TESS remains solely a subjective measure and given that it was developed almost 20 years ago, its applicability for the modern environment has been questioned. Blight and Choong in particular suggested that it should be further refined to accommodate more recent surgical innovations, 39 a common theme across most subjective methods of functional outcome assessment.…”
Section: Subjective Functional Outcome Assessmentmentioning
confidence: 99%
“…Direct comparisons of outcomes between pediatric and adult patients undergoing similar oncologic procedures are lacking 11,12 . Although it is common for a parent or guardian to provide patient-reported outcomes on the behalf of a pediatric patient, prior studies have shown that children as young as 5 years old can accurately self-report on health-related qualityof-life instruments and the results are superior to reports made by proxy [13][14][15][16] .…”
mentioning
confidence: 99%